Old-Age Pension Entitlements Mitigate Inequality: But Concentration of Wealth Remains High - Joachim R. Frick; Markus M. Grabka (Weekly Report, 2010)
Entitlements from old-age pension schemes - statutory, company, and private - represent a considerable source of wealth. For data-related reasons, analyses of the personal wealth distribution have so far failed to take this into account, however. According to recent calculations based on the 2007 data of the German Socio- Economic Panel (SOEP), the present value of total pension and state annuity entitlements (not including entitlements to provision for dependants) amounted to roughly 4.6 trillion euros. This corresponds to an average of 67,000 euros per adult. When this is combined with individuals' financial and material assets, which amount to an average of 88,000 euros, the result is a more comprehensive total net worth of more than 155,000 euros. Civil servants and retired civil servants fare better than average if this larger view is taken. This more comprehensive measurement shows considerably less inequality of wealth than traditional analyses, which refer only to financial and material assets. This is not least because of the very widespread existence of entitlements under the various old-age pension schemes with simultaneous capping based on the contribution assessment threshold for statutory pension schemes. Nevertheless, wealth continues to be highly concentrated, and the mitigating effects of old-age pension assets will likely become less important in the future. Here the effects of falling pension levels as a result of reforms in the old-age pension systems and growing gaps in earnings histories will be felt - with the risk of increasing poverty among the future elderly.
Keywords: D31; I31; 330; Wealth inequality; Pension entitlements; SOEP